AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA (STUDI DI DESA KEDUNGBETIK KECAMATAN KESAMBEN KABUPATEN JOMBANG) - Kholmi, Masiyah (Faculty of Economics and Business, University of Muhammadiyah Malang, 2016)
This research aims to analyze the management accountability of Village Fund Allocation (ADD) in Kedungbetik. This qualitative research through data reduction method, data presentation, and verification used as data analysis. The results indicate that the planning and implementation of ADD in the village of Kedungbetik is accountable, ADD planning is based on the program proposed from village and evaluated through discussion forum at the village level. Disbursement procedures and distribution of ADD in accordance the rules of Jombang Regent No. 17 of 2015, Regulation No.113 of 2014 and the allocation of funds based on priorities. Accountability report of the ADD integrated with APBDes accountability. Management constraint is lack of understanding of village officials in implementation the ADD.Keywords: Accountability , Accountability of Village, Management